UNIVERSITY STUDENTS’ EXPERIENCES ON READINESS AND UNDERSTANDING IN IMPLEMENTING THE PROGRAM OF KAMPUS MENGAJAR - Wahyuni, Riska Tama; Saleh, M Nurul Ikhsan (LPPM IKIP PGRI Pontianak, 2023)
The Kampus Mengajar program is designed to contribute to the equalization of educational quality. The aim of this research is to analyze how students perceive their readiness and understanding in implementing the program. This study was conducted in two elementary schools in the Pakem District. The research employed a qualitative approach with a case study method, collecting data through in-depth interviews and observations. Thematic analysis was used for data analysis. The findings indicate that students’ motivation to participate in the program is related to their experiences, incentives, and credit conversion. As for students’ readiness and understanding before participating in the program, it involves their prior teaching experiences, subject knowledge, and preparation provided by the program. Regarding readiness and understanding after completing assignments, it encompasses initial assignment experiences, teaching assistance, and interpersonal skills. This study contributes valuable insights for both the government implementing the program and universities for program evaluation purposes.